Development of Ecosystem-Based Educational Tourism Oriented Learning Tools in Elementary Schools Supporting SDG 4 - Rizal Rizal; Surahman Surahman; Muhammad Aqil; Asriani Asriani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To develop ecosystem-based educational tourism-oriented learning tools for elementary schools to strengthen students’ understanding of ecosystem concepts and promote environmental awareness. This initiative supports Sustainable Development Goal (SDG) 4 by encouraging quality and contextual learning experiences, while also contributing to SDG 15 through environmental conservation education. Method: The study employed a development research method with a qualitative approach. The research was conducted in elementary schools located in Pamona Puselemba District, Poso Regency. Data were collected through observation, questionnaires, and interviews involving students, teachers, and relevant stakeholders. Based on the needs analysis, ecosystem-based educational tourism learning tools were developed in the form of learning modules, teacher guides, and interactive teaching materials aligned with the elementary school curriculum. The implementation process involved classroom application and observation of student and teacher responses. Results: The developed learning tools provide opportunities for students to learn ecosystems through direct experiences by integrating local tourism potential and environmental resources. The learning approach improves students’ engagement, environmental understanding, and appreciation of natural ecosystems. Novelty: The study introduces an ecosystem-based educational tourism learning model that connects elementary education with local environmental potential. The developed learning tools provide an alternative approach to supporting sustainable education by integrating academic learning, environmental awareness, and local tourism resources.